Hf‐W chronology of a macrochondrule from the L5/6 chondrite Northwest Africa 8192. (30th September 2020) - Hellmann, Jan L.; Kruijer, Thomas S.; Metzler, Knut; Patzek, Markus; Pack, Andreas; Berndt, Jasper; Kleine, Thorsten
Abstract: A large, igneous‐textured, and 2 cm‐sized spherical object from the L5/6 chondrite NWA 8192 was investigated for its chemical composition, petrography, O isotopic composition, and Hf‐W chronology. The petrography and chemical data indicate that this object closely resembles commonly found chondrules in ordinary chondrites and is therefore classified as a "macrochondrule.* As a result of metal loss during its formation, the macrochondrule exhibits elevated Hf/W, which makes it possible to date this object using the short‐lived 182 Hf‐ 182 W system. The Hf‐W data provide a two‐stage model age for metal–silicate fractionation of 1.4 ± 0.6 Ma after Ca‐Al‐rich inclusion (CAI) formation, indicating that the macrochondrule formed coevally to normal‐sized chondrules from ordinary chondrites. By contrast, Hf‐W data for metal from the host chondrite yield a younger model age of 11 Ma after CAIs. This younger age agrees with Hf‐W ages of other type 5–6 ordinary chondrites, and corresponds to the time of cooling below the Hf‐W closure temperature during thermal metamorphism on the parent body. The Hf‐W model age difference between the macrochondrule and the host metal demonstrates that the Hf‐W systematics of the bulk macrochondrule were not disturbed during thermal metamorphism, and therefore, that the formation age of such objects can still be determined even in strongly metamorphosed samples. Collectively, this study illustrates that chondrule formation was not limited to mm‐size objects, implying that the rarity of macrochondrules reflects either that this process was very inefficient, that subsequent nebular size‐sorting decimated large chondrules, or that large precursors were rare.